Gingival crevicular fluid interleukin-36β (-1F8), interleukin-36γ (-1F9) and interleukin-33 (-1F11) levels in different periodontal disease. Issue 1 (January 2015) - Kurşunlu, Sabri Fatih; Öztürk, Veli Özgen; Han, Buket; Atmaca, Harika; Emingil, Gülnur
Abstract Background Periodontal inflammation is driven by the coordinated action of a number of factors, including the IL-1 family. Our study aimed to examine the levels of interleukin (IL)-36β, IL-36γ and IL-33 levels in gingival crevicular fluid (GCF) from patients with different periodontal diseases. Materials and methods A total of 80 subjects, 20 patients with generalized aggressive periodontitis (G-AgP), 20 patients with chronic periodontitis (CP), 20 with gingivitis and 20 periodontally healthy subjects were included. Periodontal status was evaluated by measuring probing depth, clinical attachment loss, papillary bleeding index and plaque index. GCF cytokine levels were analysed by ELISA. Results CP, gingivitis and healthy groups had similar GCF IL-36β total amount (p > 0.008). G-AgP group had elevated IL-36β total amount compared to CP group (p < 0.008). G-AgP group had similar GCF IL-36β total amount to gingivitis and healthy groups (p > 0.008). GCF IL-36γ and IL-33 total amounts of the study groups were similar (p > 0.05). Conclusions The present study demonstrated for the first time the presence of IL-36β, IL-36γ and IL-33 GCF levels with different periodontal diseases. High levels of IL-36-β in the AgP group in comparison to CP group might suggest that periodontitis in the aggressive form could be related to the increase in GCF IL-36β.